Nitrogen Mineralization and Sugarcane Growth in Soils Fertilized with Vinasse - da Silva, Amanda Manduca Rosa [UNESP] (2020)
Ethanol production is responsible for the generation of significant amounts of vinasse, a liquid organic waste that contains high concentrations of nitrogen (N). Its direct application in the soil is widely performed in agriculture, but the vinasse N transformations that occurs in the soil remains poorly understood. This study aimed at evaluating N mineralization after applying vinasse doses (0, 75 and 150 m3 ha−1) in soils with distinct textures (sandy, sandy clay and clayey). The absorption of N by sugarcane plants was also evaluated in a pot experiment, combining the same factors (doses and soils) considered in the mineralization experiment, aiming at correlating the quantities of mineralized N with the N absorbed by the plants. In the first 42 days of incubation, N immobilization was observed in all soils and vinasse doses, with higher values of mineralized N being registered in the first 14 days in the sandy soil. Furthermore, an increase in the potentially mineralizable N was observed in all soils, when increasing doses were considered, while the half-life time augmented with the escalation of the clay content in the soils. A positive correlation between absorbed N and the dry matter of sugarcane plants was found, while negative correlations were observed between absorbed N and mineralized N after 42 days, and between absorbed N and potentially mineralizable N.